Rationalizing the Molecular Design of Hole‐Selective Contacts to Improve Charge Extraction in Perovskite Solar Cells. Issue 28 (24th June 2019) - Wang, Qiong; Mosconi, Edoardo; Wolff, Christian; Li, Junming; Neher, Dieter; De Angelis, Filippo; Suranna, Gian Paolo; Grisorio, Roberto; Abate, Antonio
Abstract: Two new hole selective materials (HSMs) based on dangling methylsulfanyl groups connected to the C‐9 position of the fluorene core are synthesized and applied in perovskite solar cells. Being structurally similar to a half of Spiro‐OMeTAD molecule, these HSMs (referred as FS and DFS) share similar redox potentials but are endowed with slightly higher hole mobility, due to the planarity and large extension of their structure. Competitive power conversion efficiency (up to 18.6%) is achieved by using the new HSMs in suitable perovskite solar cells. Time‐resolved photoluminescence decay measurements and electrochemical impedance spectroscopy show more efficient charge extraction at the HSM/perovskite interface with respect to Spiro‐OMeTAD, which is reflected in higher photocurrents exhibited by DFS/FS‐integrated perovskite solar cells. Density functional theory simulations reveal that the interactions of methylammonium with methylsulfanyl groups in DFS/FS strengthen their electrostatic attraction with the perovskite surface, providing an additional path for hole extraction compared to the sole presence of methoxy groups in Spiro‐OMeTAD. Importantly, the low‐cost synthesis of FS makes it significantly attractive for the future commercialization of perovskite solar cells. Abstract : Interactions of methylammonium with methylsulfanyl groups in DFS/FS strengthen their electrostatic attraction with the perovskite surface, providing an additional path for hole extraction compared to the sole presence of methoxy groups in Spiro‐OMeTAD, which contributes to more efficient charge extraction and less accumulation of charge carriers.